Examining Oral Health and Habits in Children With Attention Deficit Hyperactivity Disorder: A Cross-sectional Study. - Mahjoub Khatibani, Seyedeh Porousha; Rabiei, Shaghayegh; Kousha, Maryam; Vejdani, Javaneh; Maleki, Arayeh; Maleki, Dina (Journal of Pediatrics Review, 2025)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent neurological disorders in children, and due to its symptoms, patients might be unable to maintain proper oral health. Objectives: In this study, the correlation between ADHD and oral health was investigated. Methods: In the current analytic cross-sectional study, 36 children with ADHD aged 12-14 years and 36 healthy children of the same age were clinically examined regarding decay-missed-filled teeth (DMF) index and the gingival bleeding index (GBI). Two bitewing radiography images were acquired from each subject; additionally, the parents completed questionnaires regarding oral habits. To analyze the data, independent t-test, chi-squared test, and the Fisher test were employed, and for calculating the values, the SPSS software, version 16.0, was used. Results: The mean DMF index in test and control groups was 7.19±3.76 and 4.97±2.37, respectively, which was statistically significant (P=0.004). The mean GBI in the test and control groups was 35.05±30.69 and 30.88±21.04, respectively. Regardless of the higher mean GBI in the test group, the difference was not significant (P=0.504). Meanwhile, bruxism was detected in 16.7% of the children in the test group, which was significant (P=0.025). Conclusion: Children diagnosed with ADHD had a higher DMF index and poor dental hygiene. Bruxism was also more commonly detected in these patients.